Situation Report: Czechoslovakia, 4 September 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Czechoslovak Response to the Helsinki Anniversary Dissident Activities Criticized The Role of the Bar in Czechoslovakia Chemicals in Agriculture and the Contamination of Food Products Problems Concerning the Production of Nuclear Plants